A Multimodal Analysis of Negation in Princess Diana’s "Panorama" Interview - Khuzaee, Shatha; Alaghbary, Gibreel Sadeq (Public Journal of Semiotics, 2025)
Stylistic analyses of negation have traditionally and predominantly focused on linguistic texts due to lack of a well-defined tool for investigating negation in multimodal texts. To fill this methodological gap, the present study integrates the critical stylistics tool of negation in written texts with Kress and van Leeuwen’s (2006) framework of visual analysis to develop a tool for the analysis of negation in multimodal texts. This tool is named the multimodal textual conceptual function of negation (MTCFN) and is used to explore how multimodal meanings of negation are constructed in Princess Diana Panorama interview, broadcasted in 1995. The analysis revealed that the co-occurrence of language and images in the same text creates a co-text that regulates and determines the meanings of negation produced by both semiotic systems. The combination of the visual affordances of gaze direction, head tilts, and different shot types and angles helps reinforce and make coherent the meanings initiated through the verbal medium, thus creating a coherent and impactful multimodal narrative. The study concludes that stylistics holds significant potential for informing approaches to the analysis of multimodal texts and recommends that further research is carried out on other multimodal text types to test the explanatory adequacy of the proposed MTCFN tool.